1981
DOI: 10.1002/pros.2990020209
|View full text |Cite
|
Sign up to set email alerts
|

Cancer serum index: A useful nonspecific test as a parameter in multimodality screening and assessment of patients with cancer of the prostate

Abstract: A satisfactory, simple test for screening and monitoring of patients with prostatic cancer is still being sought. We suggest the use of a nonspecific test in combination with other tests. The ratio of two serum proteins (alpha 1 acid glycoprotein [AGP] and prealbumin [PAB]), may be useful markers for a cancer serum index (CSI). By separating serum components by gradient polyacrylamide gel electrophoresis, staining and quantitating these proteins by scanning densitometry, and dividing the area of AGP by that of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1985
1985
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 20 publications
(8 reference statements)
0
5
0
Order By: Relevance
“…The changes in the APRPs are triggered by some cytokines, including tumor necrosis factor-a (TNF-a) and interleukins -1 and -6 (5, 6). a 1 -Acid glycoprotein was used for pre-operative detection of fixation of colorectal tumors (8), detecting and monitoring the therapy of lung cancer (9), and screening and assessment of prostate cancer (10). Walker and Gray showed that APRPs have a higher diagnostic rate for the presence of primary malignancies of the large bowel than does carcinoembryonic antigen (7).…”
Section: Introductionmentioning
confidence: 99%
“…The changes in the APRPs are triggered by some cytokines, including tumor necrosis factor-a (TNF-a) and interleukins -1 and -6 (5, 6). a 1 -Acid glycoprotein was used for pre-operative detection of fixation of colorectal tumors (8), detecting and monitoring the therapy of lung cancer (9), and screening and assessment of prostate cancer (10). Walker and Gray showed that APRPs have a higher diagnostic rate for the presence of primary malignancies of the large bowel than does carcinoembryonic antigen (7).…”
Section: Introductionmentioning
confidence: 99%
“…The KDOQI Clinical Practice Guidelines for Nutrition in Chronic Renal Failure suggest that AGP may be more specific than CRP for detecting inflammation in MD patients [32]. In our previous study [18], we calculated a prognostic inflammatory and nutritional index (PINI), a clinical assessment tool which aggregates serum CRP, AGP, prealbumin, and albumin concentrations into a single score [35], cancer serum index (CSI) [36], and prealbumin to CRP ratio to account for the multifactorial complexity of malnutrition in HD patients.…”
Section: Discussionmentioning
confidence: 99%
“…Although a certain level of ORM is present in plasma of healthy individuals [5, 6], the amount of the substance markedly elevates in patients with metastatic tumors and in severely burned patients [7-13], who are immensely susceptible to various opportunistic infections [14-16]. Similarly, these patients are known to be carriers of M2 macrophages [33, 37], which inhibit host antibacterial innate immunities [33, 38].…”
Section: Discussionmentioning
confidence: 99%
“…As compared to healthy individuals, the plasma levels of ORM in cancer patients [7, 8] and thermally injured patients [9-13] are greatly increased, and these patients are shown to be susceptible to various opportunistic infections [14-16]. ORM has been described as an inducer of M2 macrophages [17-23], which play a major role in the increased susceptibility of these patients to opportunistic infections.…”
Section: Introductionmentioning
confidence: 99%